Application of the Humanistic Model Theory Accelerated Learning Through Approach CLAY To Improve Students' Critical Thinking Skills - Kurniasih, Siti Rohmah; Hasbiyallah, Hasbiyallah (Islamic Religious Education Study Program Postgraduate Program UIN Sunan Gunung Djati Band, 2023)
Islamic education learning so far has often been trapped in conventional approaches that do not involve physical and intellectual activities, so they are unable to train students' abilities to solve critical problems logistically, quickly, and precisely. This research aims to provide alternative solutions to PAI learning problems through the application of humanistic theory, accelerated learning models through the SAVI approach, and analyzing its impact on students' critical thinking skills. This research used a qualitative descriptive method with research subjects, namely 1 PAI teacher and 20 class VIII students at Darmayanti Cimaung Middle School. Data collection is carried out through interview techniques, observation, documentation, and questionnaires, the results of which are then analyzed and compiled in the form of a research report. The research results show that the application of humanistic accelerated learning theory through the SAVI approach can improve students' critical thinking skills by 80.62% in the good category. So it can be concluded that the theory of the humanistic accelerated learning model through the SAVI approach can improve students' thinking skills.